Sinergi Perguruan Tinggi dan Petani dalam Optimalisasi Pemupukan Tanaman Padi Berbasis Uji Tanah di Dusun Ketalo, Bantul - Lintang Panjali Siwi Pambayun; Anna Kusumawati (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2025)
This community service activity was carried out in Ketalo Hamlet, Gadingsari Village, Bantul Regency, with the aim of increasing farmers' understanding of the importance of fertilization based on soil test results for rice plants. The activity began with soil sampling and laboratory analysis to determine the status of soil fertility. The results of the analysis showed that the nitrogen content was moderate, while phosphorus and potassium were low. Based on these results, fertilizer recommendations were prepared to achieve the target harvest of 6 tons/ha, using a combination of urea, SP-36, and KCl fertilizers, and supported by organic fertilizers. In addition, counseling was carried out to farmer groups regarding soil test results and the importance of balanced fertilization. The results of the questionnaire showed that most farmers had only used Phonska compound fertilizer without knowing its content and suitability to plant needs. Through this activity, farmers gained a better understanding of the concept of fertilization based on nutrient needs and expressed their readiness to try more appropriate fertilization practices. This activity is expected to increase efficiency of fertilization and agricultural productivity in a sustainable manner.